(untitled) (Research, Society and Development, 2020)
The new coronavirus causes the coronavirus disease 19 (COVID-19) and was first recognized in Wuhan, China, in December 2019. On March 11, 2020, the World Health Organization declared it a pandemic. The clinical course of COVID-19 can be classified into three stages, "early infection", "pulmonary phase" and "hyperinflammation phase", each one characterized by specific biochemical changes. The aim of this work is to describe the differences and the potential prognosis of routine blood tests in patients hospitalized in an infirmary and intensive care unit (ICU) diagnosed with COVID-19. It is a longitudinal and retrospective study in which data collection was performed through information contained in medical records. During the study period, 62 patients with confirmed SARS-CoV-2 infection were included. Of these, 32.2% required admission to the ICU and 67.8% were treated in infirmary. Among patients treated in the ICU, age, leukocytes, banded neutrophils, neutrophils, urea, creatinine, total bilirubin, LDH and D-dimer were higher compared to those who remained in the infirmary. On the other hand, hemoglobin and hematocrit in ICU patients were lower. We believe that leukocyte levels at the admission of the patient can indicate the severity of the disease and that monitoring the levels of hemoglobin, LDH and D-dimer during the hospitalization is important to assess the progression of the disease.